Targeting tumor angiogenesis and metabolism: a new perspective in pediatric thoracic tumor therapy - Lv, Yong; Shu, Fanke; Luo, Dengke; Jia, Ru; Huang, YiDong; Xu, Chang (Frontiers in Cell and Developmental Biology, 2025)
Pediatric thoracic solid tumors encompass mediastinal tumors, chest wall tumors, and lung tumors. The pathogenesis is complex, and the clinical presentation is diverse, presenting numerous challenges in diagnosis and treatment, which severely threaten the life and health of the affected children. Angiogenesis provides nutritional and oxygen support for tumor growth and metastasis, while metabolic reprogramming meets the unique energy and material demands of tumor. Both processes play key roles in pediatric thoracic tumor development. Therefore, targeting tumor vasculature could be an important therapeutic strategy, and exploring the molecular mechanisms of metabolic reprogramming may provide a theoretical foundation for targeted treatment. This review summarizes relevant experimental research on angiogenesis and metabolic reprogramming in pediatric thoracic tumors, analyzes the limitations of current research, and proposes solutions and recommendations. Through this review, we aim to provide comprehensive information about pediatric thoracic solid tumors for clinicians and researchers, promoting personalized treatment, and ultimately improve survival rates and quality of life for affected children.